Metode Terjemah al-Qur'an Lafziyah di Pondok Pesantren al-Anwar Sleman Yogyakarata - Hidayatullah Hidayatullah; Khanafi Khanafi (UIN Kiai Haji Achmad Siddiq Jember, 2022)
In this study, we will discuss the method of training the translation of the Qur'an with the lafẓiyah system in PP. Al Anwar. This method is one of the quick methods to master the content of the Koran completely and thoroughly, not just a sentence by sentence study, but at the same time studying its content which includes the study of the Arabic language. In this study, what the author wants to explore are: 1. How is the methodology of translating the Al Quran with the lafẓiyah system applied in PP. Al Anwar Sleman Yogyakarta?2. What are the supporting factors and obstacles in implementing the translation training of the Qur'an with the lafẓiyah system in PP. Al Anwar Sleman Yogyakarta? The method used in this research is descriptive qualitative, namely trying to obtain information and descriptions of how the translation training of the Al-Qur'an with the lafẓiyah system applied in PP. Al Anwar Sleman Yogyakarta. The data sources of this research are all those who are involved with the object of this research. The author uses the sample purposive so that it can take from rich sources of information used in this study. From this study, it was concluded that the training in translating the Qur'an with the lafẓiyah well , and made many positive contributions to PP students. Al Anwar Sleman Yogyakarta. One of them helps to understand the meaning of the verses of the Quran quickly.